HUMANISTIC APPROACHES IN EDUCATION SYSTEM OF THE INDUSTRIAL REVOLUTION 4.0 - Haryanto,; Siti Irene Astuti Dwiningrum, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The adaptation of humanism theory has become an essential requirement in education system due to the mobility of technology. Hence, it is important develop the students in order to assist them to face the challenges of the Industrial Revolution of 4.0. This research aims to study the application of humanistic approaches (integrative and interconnective) and its effectiveness towards the students. This research is based on qualitative method and the data is collected by using questionnaires, observation, interviews and documentation. The research subjects are teachers and students from SMAN "X" in Yogyakarta, Indonesia. The result shows that: (1) the importance of the teacher's understanding in educating the humanistic approaches to empower the student’s potentials in all dimensions, (2) the implementation of humanistic approaches in education to handle the internal and external obstacles, (3) the importance on humanistic approaches in academic field. Therefore, the humanistic approaches should be based on three powers which are: the power to, power with, power within power to enhance the student ability to overcome the challenges of the Industrial Revolution 4.0.